Trifid nasopalatine canal: case report of a rare anatomical variation and its surgical implications - Marianna Torres; Ludmila de Faro Valverde; Manuela Vidal; Iêda Crusoé-Rebello (Editorial Ciencias Médicas, 2016)
Introduction: the nasopalatine canal is a long slender structure present in the midline of the anterior maxilla that connects the palate to the floor of the nasal cavity. The nasopalatine canal contains the nasopalatine nerve, the terminal branch of the nasopalatine artery, fibrous connective tissue, adipose tissue, and minor salivary glands. Objective: the purpose of this article was to report a case of a trifid nasopalatine canal detected by cone beam computed tomography prior to dental implant placement. Case report: a 47-year-old female patient was submitted to cone beam computed tomography. Axial and sagittal sections revealed a trifurcation of the nasopalatine canal. Each canal was separated from the other by bony septa and extended independently from the floor of the nasal cavity to the incisive foramen in the remnant of the alveolar process in the anterior region of the maxilla. Cone beam computed tomography has permitted better visualization of the details and anatomical variations of the nasopalatine canal. Conclusion: detailed knowledge of variations in the shape, number and size of the nasopalatine canal is fundamental for surgical procedures, such as local anesthesia in the anterior maxillary region and placement of dental implants, in order to prevent damage to important arteries and nerves.